Lean Production Model to Increase Equipment Availability in the Manufacturing Process of Gas Hose Connectors in Metalworking SMEs - Padilla-Triveno, Jennifer (2022)
In this case study of the metal-mechanic industry located in Lima. It investigated the problems in the manufacturing line of gas hoses. As a result, lean Manufacturing tools have been proposed to increase the availability of gas hoses with the application of a Value stream mapping to analyze the current and future state of the company. Also, the 6S (safety, sort, set, sustain, shine, standardize) technique gives a correct classification, organization, cleanliness, safety, standardization, and commitment to the hose manufacturing process. In addition, work standardization was implemented to eliminate non-added values. In addition, the single-minute exchange of die technique was implemented to reduce the setup time of the manufacturing process, and finally, inventory control was implemented to reduce the delivery time of materials. As a result of the improvement model, it is intended to reduce manufacturing times and increase overall equipment efficiency (OEE).